(untitled) (Journal of the College of Basic Education, 2022)
Planning is an essential element in the educational process. As no educational work can be carried outWithout prior planning for it, it is the stage of thinking that precedes the implementation of any action, which ends with taking actionDecisions about what to do, how and when to do it. Educational planning is a serious matter and is not merely an abstraction of the educational goals that we desireIn witnessing its occurrence, it is also the actions that are taken to achieve the goals (00. The educational school buildings are among the important inputs in the educational planningPlanning for it is assumed to include both quantitative and qualitative aspects; The quantity is treatedThe numbers of students, schools, their rooms and courtyards, and the costs of their construction; The quality deals with the characteristics of the buildingAnd its terms.